An Empirical Study of the Drag Force and the Power Consumption for the Vortex Ring Generator in Aqueous CaCO3 Slurry - Kojovic, Aleksandar (My University, 1999)
The objective of this research was to investigate the affects of various generator plate size, D/d ratio, stroke frequency and slurry concentration, for a plate type vortex ring mixer, on the drag force and power consumption. In this case CaCO3 aqueous slurry was used for the investigation. The generator plate was driven using an AC induction motor with gear type speed reducer which was controlled using a frequency inverter and a mechanism for converting rotational into translational motion. This drive system resulted in sinusoidal motion of the generator plate. The applied force, the displacement of the generator plate and the input power were measured using measurement cell developed for this purpose. The viscosity was also measured. The data were analyzed, organized and presented using appropriate graphs. The force measurement data showed that drag force was mainly affected by the size of generator plate and its oscillating frequency. Larger generator plates had greater drag force acting on them and, therefore, required more power for running. Oscillating frequency had similar effect on drag force and power consumption. However, tested CaCO3 slurry concentrations showed to have no significant affect on these two parameters. Drag force results obtained during this study are considered to be reasonably representative, while power consumption data, although representative for this system, will probably be different for different drive systems employed.
Keywords: Drag Force Measurement; Plate Type Vortex Ring Mixer; Mechanical Engineering